The Influence of CSR awareness on Consumer Behavior through Trustworthiness: The New Approach: Descriptive Research Article (European Journal of Behavioral Sciences, 2020)
The goal of this research is to measure level of customer awareness of Corporate Social Responsibility (CSR) in Georgian society and to study the influence of CSR awareness on consumer behavior through trustworthiness (one of the dimensions of corporate credibility) by revealing the correlations between customer awareness and corporate trustworthiness, customer willingness to be involved in CSR initiatives and customer purchase intentions. The descriptive research was carried out and data were collected based on the survey of 915 respondents located in Tbilisi, Georgia. The relationships between variables have been studied by using multiple regressions technique. This article provides data that lead to a new conceptual model and point the importance of elevating the level of customer CSR awareness in achieving corporate credibility goals.Beyond it, customers’ inclination to purchase products from those companies who care about their long-term interest has been revealed.